PENGARUH JENIS RAGI PADA FERMENTASI KAKAO TERHADAP KARAKTERISTIK CUKA KAKAO - Wulandari, Nur Wienda Permata; Permana, Dewa Gde Mayun; Duniaji, Agus Selamet (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 3 (2019): Jurnal ITEPA, 2019)
This research was aimed to determine the effect type of “ragi” on the fermentation process of cocoa and to determine type of “ragi” that can produce vinegar with the best characteristics. This research used Randomized Block Design (RBD) with four types treatment of “ragi”, these are: without the addition of “ragi”, addition of bread yeast, addition of “tape ragi”, and addition of combination “ragi”. “Ragi” additions were carried out as much as 1% in each treatment. This research was repeated three times, resulting in 12 experimental units. The data was analyzed with Anova test and continued with Duncan test if the treatment had a significant effect (P<0.05) on the observed variable. This research showed that the treatment fermentation addition of tape ragi was the best treatment with characteristic 5.05 pH, 0.88% total acid, 3.33% total soluble solids, 0.59% total sugar and 0% alcohol. Keyword: cocoa, ragi, vinegar, fermentation